Pengaruh Elemen Sensory Branding Terhadap Perilaku Pengambilan Keputusan Konsumen Dalam Membeli Aqua Dengan Pendekatan Neuromarketing Di Kabupaten Jember - Dimas Khurniawan; Mohammad Dimyati; Deasy Wulandari (UPT Penerbitan Universitas Jember, 2017)
The purpose of this study acclaims the important of Auditory, Visual and Tactile in affecting consumerâ€™s decision makingbehavior of buying, it is also to figure out itâ€™s impact in Aqua. Thus, it is important to study â€œThe Impact Of SensoryBrandingâ€™s Elements On Consumerâ€™s Decision Making Behavior Of Buying Aqua With Neuromarketing Approach InJemberâ€. The population in this study are Aquaâ€™s consumers in Jember. Sampling is taken using purposive sampling methodfrom 100 respondents. Instrument analysis in this study is performed using Structural Equation Model (SEM) withconfirmatory approach. The result shows that: 1) auditory significantly affects consumerâ€™s decision making behavior of buyingAqua in Jember, 2) visual significantly affects consumerâ€™s decision making behavior of buying Aqua in Jember, and 3) tactilesignificantly affects consumerâ€™s decision making behavior of buying Aqua in Jember.